The performance of ETFs on developed and emerging markets with consideration of regional diversity - Krystian Zawadzki (Quantitative Finance and Economics, 2020)
This study evaluates the performance of Exchange-Traded Funds (ETFs) by using various tracking error calculation approaches. The aim of the paper is, on the one hand, an evaluation of the performance of ETFs relative to their benchmarking indexes and, on the other, an endeavour to specify any relationship between this performance and both geographical location and the degree of market development. The research was conducted on the basis of 18 different ETFs issued by iShares, six for each of three regions: both Americas, Asia and Europe. The sole criterion for ETF's selection was the benchmark. All data were collected with daily frequency. They range from January 2013 to December 2019. The results indicate that ETFs do not mimic their corresponding indexes well. Calculated tracking errors do not equal zero and are often significantly negative. Furthermore, the value of tracking errors depends on the region and the degree of market development.